Cytotoxicity and photocytotoxicity of a dendritic C60 mono-adduct and a malonic acid C60 tris-adduct on Jurkat cells - Rancan, Fiorenza; Rosan, Stefania; Böhm, Fritz; Cantrell, Ann; Brettreich, Michael; Schönberger, Hubert; Hirsch, Andreas; Moussa, Fathi (Journal of Photochemistry and Photobiology B-Biology, 2002)
The cytotoxic and photocytotoxic effects of two water-soluble fullerene derivatives, a dendritic C mono-adduct and the malonic acid C tris-adduct were tested on Jurkat cells. Cell growth and vitality were determined by a cell counting and staining technique. After 2 weeks cultivation in the presence of the fullerene derivatives, it was found that only the dendritic mono-adduct inhibits cell growth (within 2 weeks the cell number decreased to 19%), whereas the tris-malonic acid adduct has little effect. The growth inhibition is reversible; cultivating the same cells further in the absence of fullerene, the cell number increased to 106.4%. Other experiments showed that these fullerene derivatives become toxic when irradiated with UVA or UVB light. The cell death is mainly caused by membrane damage and it is UV dose-dependent. Tris-malonic acid fullerene was found to be more phototoxic than the dendritic derivative. This result is in contrast to the singlet oxygen quantum yields determined for the two compounds. We propose that the two fullerene derivatives may interact with the cell membrane in different ways thus causing the observed effects. Further experiments will be done to determine the location and concentration of the two compounds in and on the cells. © 2002 Elsevier Science B V All rights reserved.